Caribbean biogeography: molecular evidence for dispersal in West Indian terrestrial vertebrates. - Hedges, S B (1992)
The geological association of the Greater Antilles with North and South America in the late Cretaceous led to the hypothesis that the present Antillean biota reflects those ancient land connections. Molecular data from diverse West Indian amphibians and reptiles and their mainland relatives support a more recent derivation of the Antillean vertebrate fauna by overwater dispersal. The catastrophic bolide impact in the Caribbean region at the close of the Cretaceous provides a proximate cause for the absence of an ancient West Indian biota.